2008
DOI: 10.1007/s10404-008-0275-7
|View full text |Cite
|
Sign up to set email alerts
|

Flow characterization of valveless micropump using driving equivalent moment: theory and experiments

Abstract: A valveless micropump, actuated by a PZT disk bonded to a glass plate, can generate positive flow. In order to estimate flow characteristics of micropumps, it is necessary to theoretically analyze the radial expansion (more specifically, the equivalent moment) of the PZT disk according to the voltage input. Using the equivalent moment, deflection equations are derived for the tri-layer disk (PZT, epoxy bonder and glass plate) and are confirmed to match well with experiments. The flow rate of the valveless micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Two main types of fixed microvalves have been used in valveless micropumps which are microdiffusers (Stemme and Stemme 1993;Gerlach et al 1995;Olsson et al 1999;Pan et al 2001;Schabmueller et al 2002;Yang et al 2004a;Jeong and Kim 2007;Sun and Yang 2007;Hwang et al 2008;Nabavi and Mongeau 2009) and Tesla microvalves (Forster et al 2001;Feldt and Chew 2002;Morris and Forster 2003). In fixed microvalves wear and fatigue in the valves are eliminated since they have no moving parts.…”
Section: Microscale Fluid Rectification: Microvalvesmentioning
confidence: 98%
See 1 more Smart Citation
“…Two main types of fixed microvalves have been used in valveless micropumps which are microdiffusers (Stemme and Stemme 1993;Gerlach et al 1995;Olsson et al 1999;Pan et al 2001;Schabmueller et al 2002;Yang et al 2004a;Jeong and Kim 2007;Sun and Yang 2007;Hwang et al 2008;Nabavi and Mongeau 2009) and Tesla microvalves (Forster et al 2001;Feldt and Chew 2002;Morris and Forster 2003). In fixed microvalves wear and fatigue in the valves are eliminated since they have no moving parts.…”
Section: Microscale Fluid Rectification: Microvalvesmentioning
confidence: 98%
“…Flow rate increased with increasing the frequency. Hwang et al (2008) developed a numerical model using ANSYS to evaluate the flow rate of a reciprocating valveless micropumps. They compared their calculated results with the experimental data with respect to the peakto-peak voltage (V pp ) and the driving frequency (f).…”
Section: Flow Separationmentioning
confidence: 99%
“…Pan et al (2001) suggested an optimal frequency range for reciprocating valveless micropumps based on an analytical model. Hwang et al (2008) developed a numerical model using ANSYS to evaluate the flow rate of a reciprocating valveless micropumps. Tsui and Lu (2008) analyzed the flow in a reciprocating valveless micropump using both numerical and lumpedelement methods.…”
Section: Introductionmentioning
confidence: 99%
“…The valveless type rectifiers generate a net flow based on a direction-dependent resistance. Some examples, such as the nozzle/diffuser element Olsson et al 2000;Hwang et al 2008), the Tesla structure (Gamboa et al 2006), and a combination form of nozzle/diffuser and Tesla structure (Izzo et al 2007), show that the flow can be pumped out using these simple-patterned designs.…”
Section: Introductionmentioning
confidence: 97%